PENINGKATAN KEMAMPUAN BERBICARA MAHASISWA MENGGUNAKAN METODE PROJECT BASED LEARNING MELALUI PEMBUATAN PODCAST - Safitri, Nuzul Hijrah; Nuru, Sarniati; Nugraha Silawati, Aminah Maulidah; Nurjannah, Nurjannah; Ruhhiyah, Muh. Al-Yaqzathur (STKIP Paris Barantai, 2025)
This research was Classroom Action Research (CAR) that aimed to investigate the implementation of PjBL method in speaking class through generating English Podcast and to find out students’ perception on the application of PjBL method and English podcast project in speaking class. This research was conducted in 2 cycles by involving 37 students of English Literature Study Program, Universitas Halu Oleo and by using Kemmis and Mc Taggart (1988) model. The data were collected through observing, interviewing and doing speaking test. The results of cycle 1 showed that there was 27,03% of total students who achieved the Minimum Mastery Criteria with the mean score of 61,02. However, in the cycle 2, there was 94,60% of total students who achieved the Minimum Mastery Criteria with the mean score of 72,08. The results indicated that the implementation of PjBL through generating English Podcast in Speaking class could improve students’ speaking skill. Moreover, students perceived positively the application of PjBL through creating English podcast project. The PjBL method gets students actively involved in the learning process, encourages them to think creatively and improves their collaboration and communication skills as they work on the project. Keywords: Project Based Learning, Podcast, Speaking Skill